Respuesta :

Equation  By Substitution/Elimination  Method:

y   =    -3x    +    4;      y    =    4x     -    10

Let's solve your system by substitution.

y     =     −3x     +    4;       y     =    4x    −    10

Step: Solve       y      =     −3x    +     4     for y:

y       =      −3x       +      4

Step: Substitute      −3x      +    4     for     y     in     y    =     4x     −    10:

y     =     4x    −    10

−3x      +     4     =     4x    −    10

−3x      +     4    +        −4x       =4x     −   10    +    −4x   (Add -4x to both sides):

−7x      +     4     =     −10

−7x      +     4     +      −4     =     −   10    +    −4     (Add -4 to both sides):

-7x        =      -14

-7x/ -7     =     -14/ -7   ( Divide both sides by  -7):

x      =      2

Step 2:  Substitute         2        for     x      in       y     =     −3x    +    4:

y      =       −3x     +    4

y       =    (−3)(2)     +     4

y       =        −2         (Simplify both sides of the equation)

Answer:

x    =     2       and       y       =      −2



Hope that helps!!!!









Ver imagen claudettoterohil